José Ramón Álvarez Layna (ed.) (2015), Robert Owen: textos del socialista utópico - Cueva Fernández, Ricardo (EUNOMÍA. Revista en Cultura de la Legalidad, 2016)
doi: http://dx.doi.org/10.20318/eunomia.2016.3301